Suture Tape-Reinforced Human Dermal Allograft Used for Superior Capsule Reconstruction Demonstrates Improved Ability to Withstand Elongation - Cody S. Lee, M.D; Manoj Reddy, M.D; Bryan Scott, M.D; Daniel Curtis, M.D; Farid Amirouche, Ph.D; Aravind Athiviraham, M.D (Elsevier, 2020)
Purpose: To investigate the potential for a suture tape-reinforcement technique to prevent elongation with repetitive use of a human dermal (HD) allograft traditionally used for superior capsule reconstruction in a biomechanical model. Methods: Using 8 scapulae and humeri Sawbones models, the standard superior capsule reconstruction was performed using 8 HD allografts. Four grafts were tested in the native state, whereas 4 were tested using reinforcement. Allografts were reinforced using suture tape in a running 360° fashion around the allograft borders, maintaining 5 mm of space from the edges. Allografts were measured pre- and postdynamic testing for length, width, and thickness. All specimens were affixed to a materials testing machine that allowed for allograft orientation in a longitudinal plane throughout testing. Specimens were preloaded to 10 N and then cyclically loaded to 100 N at a rate of 15 mm/s for 30 cycles. Results: After dynamic, cyclic loading, suture tape-reinforced allografts experienced a significantly smaller percent change in anterior length (6.36% vs 14.50%, P = .013), posterior length (6.00% vs 13.68%, P = .002), medial width (5.80% vs 21.05%, P = .001), lateral width (5.45% vs 19.29%, P < .001), medial thickness (4.38% vs 17.93%, P = .005), central thickness (7.03% vs 16.11%, P = .026), and lateral thickness (4.55% vs 20.80%, P < .001). Linear stiffness values obtained for suture tape -reinforced allografts were significantly greater than those for native allografts when measured at cycles 1 (21.18 ± 1.03 N/mm vs 17.69 ± 1.91 N/mm, P = .02), 15 (29.90 ± 1.45 vs 24.93 ± 2.79, P = .03), and 30 (32.13 ± 1.98 N/mm vs 25.72 ± 3.01 N/mm, P = .01) of dynamic testing Conclusions: The suture tape-reinforcement technique described decreased HD allograft elongation, maintained graft thickness, and improved linear stiffness values following uniplanar cyclic loading in a biomechanical Sawbones model. Clinical relevance: Suture tape reinforcement of the HD allograft could serve as one strategy to overcome the issue of allograft elongation with time following superior capsule reconstruction.